A rigid waterproof coating with adjustable thickness and its preparation method and application

By adding a fixed thickness material to the cement-based permeable crystalline waterproof coating, the problems of coating thickness uniformity and controllability are solved, real-time thickness monitoring and adjustment during construction are achieved, the risks of appearance defects and degraded waterproof performance are reduced, and the waterproof performance requirements of relevant standards are met.

CN117070089BActive Publication Date: 2025-03-21QINGDAO MOCO ENVIRONMENTAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311158004.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21
Estimated Expiration
2043-09-08

AI Technical Summary

Technical Problem

It is difficult to achieve uniformity and control of the coating thickness during construction of existing cement-based permeable crystalline waterproof coatings, resulting in appearance defects and degradation of waterproofing performance.

Method used

Add a fixed thickness material to cement-based permeable crystalline waterproof coating. The particle size range of the fixed thickness is 90% to 120% of the coating design thickness requirements to ensure that the coating can visually measure the thickness in real time and adjust it during construction, reducing uneven thickness and appearance defects.

Benefits of technology

By adding a fixed thickness material, the uniformity of coating thickness and controllability of construction quality are achieved, uneven thickness and appearance defects after hardening are reduced, and the waterproof performance requirements of GB18445-2012 standard are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117070089B_ABST
    Figure CN117070089B_ABST
Patent Text Reader

Abstract

The invention discloses a rigid waterproof coating with adjustable thickness, comprising 2-20 parts of infiltration crystallization active masterbatch, 40-70 parts of cement, and 20-40 parts of 60-140 mesh refined quartz sand; and also comprising a thickness-adjusting material, wherein the thickness-adjusting material is granular, and the particle size range of the granular thickness-adjusting material is 90% to 120% of the required value of the coating design thickness; and the mass fraction of the thickness-adjusting material in the waterproof coating is less than 5wt%. The thickness-adjusting material has a narrow particle size distribution, and its particle size matches the coating thickness requirement. Therefore, during the scraping or smearing construction process, the thickness of the thickness-adjusting material is equivalent to the coating thickness, which is convenient for controlling the slightly poor application quality of the base layer, reducing the appearance defects such as pits and holes that appear after hardening, and the coating thickness is uniform; the performance meets the requirements of GB18445-2012 standard; and it is also conducive to the later construction quality acceptance control, and there is no need to cut or destroy the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waterproof coatings, and in particular to a rigid waterproof coating with adjustable thickness, a preparation method thereof and an application thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Waterproof coatings are generally divided into two categories. One category is mainly reactive polymers, polymer emulsions and water-based polymer asphalt waterproof coatings, which have the characteristics of good film-forming and elongation performance. The other category is rigid waterproof coatings based on cement-based materials, which have the characteristics of high strength and durability, and are synchronized with the life of the main structure. Cement-based penetrating crystallization waterproof materials (hereinafter referred to as CCCW) are one of the typical rigid waterproof materials. Among them, cement-based penetrating crystallization waterproof coating type C (CCCW C) is a new type of rigid waterproof material made of silicate cement or ordinary silicate cement, refined quartz sand (60-140 mesh, or compounded with finer quartz sand) as the base material, and active chemical substances (i.e. penetrating crystallization active masterbatch) are added. The mechanism of action of CCCW C waterproof coating is that after the material is brushed with water, the active chemical substances contained in the material, with the help of cement slurry, penetrate into the interior of the structural concrete through complex reaction precipitation, form water-insoluble crystals in the concrete, block the capillary channels, and make the concrete dense and waterproof.

[0004] The construction requirements of CCCW C-type coatings are generally based on the design requirements of coating film thickness. In actual applications, considering that the specific gravity / bulk density of finished materials in the process of preparing coatings with different brands of masterbatches is not much different, based on practical experience, the application amount is uniformly added as the control indicator of the application operation. The current standards GB 50108-2008 and GB 55030-2022 both require that the amount of cement-based penetrating crystalline waterproof coatings should not be less than 1.5kg / m 2 , and the thickness should not be less than 1.0mm.

[0005] On the premise that product quality meets standard requirements, coating thickness is the key control item for functional coatings. For the inspection and acceptance of waterproof layer coating thickness, the current standard GB 50208-2011 requires the use of the needle test method. However, the needle test method is only applicable to flexible coatings. For rigid coatings, the probe cannot penetrate after hardening and curing. At the same time, the coating of rigid coatings cannot be tested by cutting. When mechanical tools are used to cut deeply together with the base layer, the coating thickness cannot be accurately distinguished due to the similar color of the base layer and the coating. This is also the reason why the existing standards have additional control over the unit material usage of rigid materials during construction, that is, to ensure that the coating thickness meets the requirements by limiting the usage.

[0006] However, in the actual construction process, due to the influence of various human and environmental factors, the ideal working conditions required by relevant specifications are often not achieved. CCCW C-type waterproof materials are prone to appearance defects such as roughness, pits, and poor flatness. The coating is not uniform after film formation, and the coating thickness is uneven, which affects the penetration depth of active chemicals and the amount of new crystals formed, thereby weakening the overall protective ability of CCCW C-type waterproof coatings. Summary of the invention

[0007] In view of this, the present invention provides a rigid waterproof coating with adjustable thickness, a preparation method and an application thereof. During the construction process of the rigid waterproof coating, it is convenient to visually check the thickness in real time and repair the coating in real time, which is convenient for construction quality acceptance control. The coating thickness is uniform, and there are fewer appearance defects such as potholes after hardening. The performance of the waterproof material meets the requirements of GB18445-2012 standards.

[0008] In the first aspect, the present invention provides a rigid waterproof coating with adjustable thickness, comprising the following raw materials in parts by weight: 2-20 parts of infiltration crystallization active masterbatch, 40-70 parts of cement, and 20-40 parts of 60-140 mesh refined quartz sand; also comprising a granular thickness-setting material, the particle size range of the granular thickness-setting material being 90% to 120% of the required value of the coating design thickness; the mass fraction of the thickness-setting material in the rigid waterproof coating with adjustable thickness is less than 5wt%, excluding 0wt%.

[0009] The fineness requirement for CCCW C waterproof coating in the main technical indicators of the current standard is: fineness (0.63mm sieve residue) ≤ 5%. At the same time, the design thickness of the coating during the construction of CCCW C waterproof coating is not less than 1mm, so the mass fraction of the thickness-fixing material in the present invention is set to be less than 5wt%. Relevant tests show that the 0.63mm sieve residue of CCCW C waterproof coating is less than 1%, so the mass fraction of the thickness-fixing material in the rigid waterproof coating with adjustable thickness is further preferably less than 4wt%. In order to give full play to the thickness-fixing effect of the thickness-fixing material, it is further preferably 4wt%.

[0010] As a preferred embodiment of the present invention, when the design thickness of the coating is required to be no less than 1 mm, the mesh number of the thickness-fixing material is 16-18 meshes.

[0011] As a preferred embodiment of the present invention, when the design thickness of the coating is required to be no less than 1.5 mm, the mesh number of the thickness-fixing material is 12-14 meshes.

[0012] The present invention does not make any special limitation on the active masterbatch for penetrating crystallization, and conventional commercially available products may be used. The active chemical substances contained therein can penetrate into the gaps in the internal structure of the structural concrete after reacting with water, and interact with the free calcium oxide in the concrete to generate water-insoluble dendritic fiber crystals, which block the capillary pores and make the concrete dense and waterproof.

[0013] As a preferred embodiment of the present invention, the thickness determining material is selected from quartz sand or machine-made sand, preferably quartz sand. The quartz sand is preferably river sand or sea sand. The particle structure of river sand is more regular and the chloride ion content is extremely low, so river sand is preferably used; desalinated sea sand or machine-made sand with a regular shape after shaping treatment can also be selected.

[0014] As another preferred embodiment of the present invention, the thickness-setting material is selected from polymer materials. Since polymer materials do not react adversely with materials such as cement, they can also be selected as thickness-setting materials. The polymer materials include alkali-resistant polymer particles or polymer fiber chopped rods, and the alkali-resistant polymer particles are preferably polyethylene particles or polypropylene particles; the polymer fiber chopped rods are preferably polyethylene rods, polypropylene rods, polyoxymethylene rods or nylon rods.

[0015] Preferably, the cement is silicate cement or ordinary silicate cement.

[0016] In the second aspect, the present invention provides a method for preparing the above-mentioned rigid waterproof coating with adjustable thickness, comprising the following steps: putting the infiltration crystallization active masterbatch, cement and 60-140 mesh refined quartz sand into a mixing mixer in proportion, and then adding the adjustable thickness material, and continuing to stir the materials evenly to obtain the coating.

[0017] Preferably, the stirring speed before adding the thickness-fixing material is 20-70 rpm, and the stirring time is 2-5 min; the stirring speed after adding the thickness-fixing material is 50-150 rpm, and the stirring time is 2-10 min.

[0018] In a third aspect, the present invention provides a construction method for a rigid waterproof coating with adjustable thickness, specifically, the powdered rigid waterproof coating with adjustable thickness obtained by the above preparation method is added with water at a ratio of 1:0.30 to 0.40 between the solid and liquid ratios, stirred evenly, and then the waterproof coating is applied on a flat base surface with a scraper to form a waterproof coating, and the application is completed within 20 minutes.

[0019] Preferably, the stirring time is 5 to 30 minutes.

[0020] In a fourth aspect, the present invention provides an application of the above-mentioned rigid waterproof coating with adjustable thickness in a building waterproof coating.

[0021] It can be seen from the above technical solution that the present invention has achieved the following beneficial effects:

[0022] (1) The present invention adds a thickness-fixing material to the cement-based penetrating crystallization waterproof coating. The thickness-fixing material has a specific narrow particle size distribution, and its particle size matches the thickness required by the coating design. Therefore, during the scraping or smearing construction process, a little pressure is applied, and the thickness of the thickness-fixing material is the coating thickness, and the coating can also adhere well to the base layer. On the other hand, it is convenient to control the slightly poor coating quality of the base layer, and the thickness can be visually inspected in real time during the construction process and the coating can be repaired in real time, reducing the appearance defects such as uneven thickness and local pits after hardening, so that the coating thickness is uniform; in addition, it is also conducive to the later construction quality acceptance control, and there is no need to cut or destroy the coating.

[0023] (2) The convex points naturally formed on the coating surface by the thickness-fixing material added in the present invention increase the surface roughness of the coating film, which is beneficial to the bonding of cement-based materials such as mortar and concrete applied in subsequent processes;

[0024] (3) The addition of the thickness-fixing material of the present invention does not affect the permeability and crystallization performance, and has no significant effect on other technical indicators of the waterproof coating. The performance of the material meets the requirements of the standard GB18445-2012 "Cement-based Permeability and Crystallization Waterproof Material". BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 are cross-sectional images of the coatings of Examples 1 and 2 of the present invention and Comparative Examples 1 and 2; wherein A is a cross-sectional image of the coating of Example 1, B is a cross-sectional image of the coating of Comparative Example 1, C is a cross-sectional image of the coating of Example 2, and D is a cross-sectional image of the coating of Comparative Example 2;

[0027] Figure 2 These are photos of the coating surfaces of Example 1 and Comparative Example 1 of the present invention and photos of the surfaces after roughening treatment. DETAILED DESCRIPTION

[0028] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0029] The PO 42.5 ordinary Portland cement, PO 52.5 ordinary Portland cement, well-graded quartz sand with different technical requirements, polypropylene particles, and polyoxymethylene rods used in the following specific embodiments of the present invention can all be purchased through regular channels. There is no special restriction on the sources of the above raw materials.

[0030] CCA and TC infiltration crystallization active masterbatches are produced by Nanjing Crema Technology Co., Ltd.

[0031] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product instructions shall be followed.

[0032] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0033] Example 1

[0034] Put 65 parts of PO 42.5 ordinary Portland cement, 25 parts of 70-120 mesh refined quartz sand, and 6 parts of CCA infiltration crystallization active masterbatch into a mixing mixer, stir at 60 rpm for 3 minutes, then add 4 parts of 16-18 mesh quartz sand, and continue stirring for 3 minutes to obtain a powdery waterproof coating.

[0035] Stir the powdered waterproof coating for 5 minutes at a ratio of powdered waterproof coating to water = 1:0.35 until it is uniform. Use a scraper to apply the coating on the flat base surface. Calculated from the time water is added, the application should be completed within 20 minutes, and the coating thickness should be 1mm.

[0036] Example 2

[0037] Put 56 parts of PO 52.5 ordinary Portland cement, 25 parts of 60-100 mesh refined quartz sand, and 16 parts of TC infiltration crystallization active masterbatch into a mixing mixer, stir at 60 rpm for 3 minutes, then add 3 parts of 12-14 mesh quartz sand, and continue stirring for 3 minutes to obtain a powdery waterproof coating.

[0038] Stir the powdered waterproof coating for 5 minutes at a ratio of powdered waterproof coating to water = 1:0.35 until it is uniform. Use a scraper to apply the coating on the flat base surface. Calculated from the time water is added, the application should be completed within 20 minutes, and the coating thickness should be 1.5mm.

[0039] Example 3

[0040] Put 65 parts of PO 42.5 ordinary Portland cement, 25 parts of 70-120 mesh refined quartz sand, and 6 parts of CCA infiltration crystallization active masterbatch into a mixing mixer, stir at 60 rpm for 3 minutes, then add 4 parts of 16-18 mesh polypropylene particles, and continue stirring at 120 rpm for 2 minutes to obtain a powdery waterproof coating.

[0041] Stir the powdered waterproof coating for 5 minutes at a ratio of powdered waterproof coating to water = 1:0.35 until it is uniform. Use a scraper to apply the coating on the flat base surface. Calculated from the time water is added, the application should be completed within 20 minutes, and the coating thickness should be 1mm.

[0042] Example 4

[0043] Put 56 parts of PO 52.5 ordinary Portland cement, 25 parts of 60-100 mesh refined quartz sand, and 16 parts of TC infiltration crystallization active masterbatch into a mixing mixer, stir at 60 rpm for 3 minutes, then add 3 parts of 12-14 mesh polyoxymethylene rods with an aspect ratio of 1, and continue stirring for 3 minutes to obtain a powdery waterproof coating.

[0044] Stir the powdered waterproof coating for 5 minutes at a ratio of powdered waterproof coating to water = 1:0.35 until it is uniform. Use a scraper to apply the coating on the flat base surface. Calculated from the time water is added, the application should be completed within 20 minutes, and the coating thickness should be 1.5mm.

[0045] Comparative Example 1

[0046] Put 65 parts of PO 42.5 ordinary Portland cement, 29 parts of 70-120 mesh refined quartz sand, and 6 parts of CCA penetration crystallization active masterbatch into a mixing mixer, and stir at 60 rpm for 6 minutes to obtain a powdery waterproof coating.

[0047] Apply powder waterproof coating at 1.5kg / m 2 The dosage is based on the ratio of powdered waterproof coating to water = 1:0.35. Stir for 5 minutes until it is uniform, and use a scraper to apply the coating on the flat base surface. Calculated from the time when water is added, the application should be completed within 20 minutes.

[0048] Comparative Example 2

[0049] Put 56 parts of PO 52.5 ordinary Portland cement, 28 parts of 60-100 mesh refined quartz sand, and 16 parts of TC infiltration crystallization active masterbatch into a mixing mixer, and stir at 60 rpm for 6 minutes to obtain a powdery waterproof coating.

[0050] Apply powder waterproof coating at 2.1kg / m 2The dosage is based on the ratio of powdered waterproof coating to water = 1:0.35. Stir for 5 minutes until it is uniform, and use a scraper to apply the coating on the flat base surface. Calculated from the time when water is added, the application should be completed within 20 minutes.

[0051] Comparative Example 3

[0052] Put 65 parts of PO 42.5 ordinary Portland cement, 29 parts of 70-120 mesh refined quartz sand, and 6 parts of CCA infiltration crystallization active masterbatch into a mixing mixer, and stir at 60 rpm for 5 minutes to obtain a powdery waterproof coating.

[0053] Apply powder waterproof coating at 1.5kg / m 2 The dosage is powdered waterproof coating: water = 1:0.35 ratio, stir for 5 minutes until it is uniform, and apply the coating on the flat base surface with a scraper. Calculated from the time of adding water, the application should be completed within 20 minutes.

[0054] Comparative Example 4

[0055] Put 56 parts of PO 52.5 ordinary Portland cement, 28 parts of 60-100 mesh refined quartz sand, and 16 parts of TC infiltration crystallization active masterbatch into a mixing mixer, and stir at 60 rpm for 6 minutes to obtain a powdery waterproof coating.

[0056] Apply powder waterproof coating at 2.1kg / m 2 The dosage is powdered waterproof coating: water = 1:0.35 ratio, stir for 5 minutes until it is uniform, and apply the coating on the flat base surface with a scraper. Calculated from the time of adding water, the application should be completed within 20 minutes.

[0057] Test example

[0058] A small piece of coating with a base layer was broken longitudinally, and a relatively straight cross-section portion was selected for microscope observation and photographing. The thickness of the coatings of Examples 1-2 and Comparative Examples 1-2 was measured, counted and analyzed using Image J software, and the results are shown in Table 1.

[0059] Table 1 Coating thickness measurement results of Examples 1-2 and Comparative Examples 1-2

[0060]

[0061]

[0062] As can be seen from Table 1, Examples 1 and 2 and Comparative Examples 1 and 2 all meet the requirements of the response design thickness, and there is no point lower than 90% of the design thickness, but the adjustable thickness coating thickness of Examples 1 and 2 is more accurately close to the design thickness requirement, with a deviation of less than 10%, while the coating thickness of Comparative Examples 1 and 2 is about 20% higher than the design thickness requirement. The mean square error results also show that the uniformity of the adjustable thickness coating thickness of Examples 1 and 2 is much better than the coating thickness of Comparative Examples 1 and 2.

[0063] Figure 1 A is a cross-sectional photo of the coating of Example 1, B is a cross-sectional photo of the coating of Comparative Example 1, C is a cross-sectional photo of the coating of Example 2, and D is a cross-sectional photo of the coating of Comparative Example 2. It should be noted that for clear shooting, the magnification is not exactly the same, so the sizes in the figures cannot be used for comparison reference. Figure 1 It can be seen that the coatings of Example 1 and Example 2 are more uniform in thickness than those of Comparative Example 1 and Comparative Example 2.

[0064] Figure 2 The following are photos of the coating surfaces of Example 1 and Comparative Example 1, as well as the surfaces after roughening treatment. It can be seen that the adjustable thickness coating surface prepared in Example 1 has convex points, and the surface around the convex points is relatively flat, while the coating surface of Comparative Example 1 is smoother, with a larger area of ​​depressions. The roughening treatment of the two coatings shows that the adjustable thickness coating prepared in Example 1 has a rougher surface, which is more conducive to later bonding.

[0065] According to GB18445-2012 standard, performance tests were performed on Examples 1-4 and Comparative Examples 1-4, and the results are shown in Table 2 (Note: the 28d impermeability pressure of the reference mortar and reference concrete is 0.3 MPa); and paired double-sample t-tests were performed on the examples and comparative examples one by one, and the results are shown in Table 3.

[0066] Table 2 Physical and chemical properties test results of coatings of Examples 1-4 and Comparative Examples 1-4

[0067]

[0068]

[0069] The test results in Table 2 show that the coating properties of Examples 1-4 all meet the standard requirements, indicating that the addition of the thickness-setting material does not significantly affect other properties of the coating.

[0070] Table 3 Paired two-sample t-test results

[0071]

[0072] It can be seen from Table 3 that the P values ​​are all greater than 0.05, indicating that there is no significant difference between the embodiments and the corresponding comparative examples; in addition, it can be seen that when the round plastic material is used as the thickness material, its P value is slightly greater than 0.05, close to the critical value, but it can still be considered that there is no significant difference.

[0073] The present invention is aimed at rigid waterproof coatings, especially cement-based penetrating crystalline waterproof coatings, and the coating thickness setting during construction. In view of the fact that cement-based penetrating crystalline waterproof coatings are rigid coatings, the addition of thickness setting materials can well solve the problem of rigid coating thickness setting. Therefore, it can be further understood that it can be expected that the thickness setting materials of the present invention can also play a corresponding thickness setting role in the coating thickness setting of other rigid waterproof coatings, waterproof mortars, plastering mortars, etc.

[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A rigid waterproof coating with adjustable thickness, characterized in that: The invention comprises the following raw materials in parts by weight: 2-20 parts of infiltration crystallization active masterbatch, 40-70 parts of cement, and 20-40 parts of 60-140 mesh refined quartz sand; and also comprises granular thickness-setting materials, wherein the particle size range of the granular thickness-setting materials is 90% to 120% of the required value of the coating design thickness; the mass fraction of the thickness-setting materials in the rigid waterproof coating with adjustable thickness is less than 5wt%, excluding 0wt%; The thickness-setting material is selected from quartz sand, machine-made sand or polymer material, and the polymer material includes alkali-resistant polymer particles or polymer fiber chopped rods; the aspect ratio of the polymer fiber chopped rods is 1.

2. The adjustable thickness rigid waterproof coating according to claim 1, characterized in that: The mass fraction of the thickness-setting material in the thickness-setting rigid waterproof coating is less than 4wt%.

3. The adjustable thickness rigid waterproof coating according to claim 2, characterized in that: The mass fraction of the thickness-setting material in the thickness-setting rigid waterproof coating is 4wt%.

4. The adjustable thickness rigid waterproof coating according to claim 1, characterized in that: The alkali-resistant polymer particles are polyethylene particles or polypropylene particles, and the polymer fiber chopped rods are polyethylene rods, polypropylene rods, polyoxymethylene rods or nylon rods.

5. A method for preparing a rigid waterproof coating with adjustable thickness as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following steps: putting the infiltration crystallization active masterbatch, cement and 60-140 mesh refined quartz sand into a mixing mixer according to proportion, and then adding the thickness setting material, and continuing to mix the materials evenly to obtain the product.

6. The preparation method according to claim 5, characterized in that: The stirring speed before adding the thickness-fixing material is 20-70 rpm, and the stirring time is 2-5 min; the stirring speed after adding the thickness-fixing material is 50-150 rpm, and the stirring time is 2-10 min.

7. A construction method for a rigid waterproof coating with adjustable thickness, characterized in that: The powdery rigid waterproof coating with adjustable thickness obtained by the preparation method according to claim 5 or 6 is added with water at a ratio of 1:0.30-0.40, stirred evenly, and then the waterproof coating is applied on a flat base surface with a scraper to form a waterproof coating, and the application is completed within 20 minutes.

8. Use of the adjustable-thickness rigid waterproof coating as claimed in any one of claims 1 to 4 in building waterproof coatings.

Citation Information

Patent Citations

  • Efficient cementitious capillary crystalline waterproofing coating as well as preparation method and construction method thereof

    CN103755286A

  • Hard coating composition

    CN104039903A

  • Material of cement-base for covering surface of bridge

    CN1559971A